Wnt Signaling and Biological Therapy in Rheumatoid Arthritis and Spondyloarthritis - Cici, Daniela (Int J Mol Sci, 2019)
The Wnt signaling pathway plays a key role in several biological processes, such as cellular proliferation and tissue regeneration, and its dysregulation is involved in the pathogenesis of many autoimmune diseases. Several evidences support its role especially in bone complications of rheumatic diseases. In Rheumatoid Arthritis (RA), the Wnt signaling is implicated in systemic and localized bone loss, while available data of its role in Spondyloarthritis (SpA) are conflicting. In the last few decades, the quality of life of rheumatic patients has been dramatically improved by biological therapy, targeting cytokines involved in the pathogenesis of these diseases like tumor necrosis factor (TNF)α, interleukin (IL)-1, IL-6, IL-17. In this review, we reviewed the role of Wnt signaling in RA and SpA, focusing on the effect of biological therapy on this pathway and its possible clinical implications.